(untitled) (Academicia Globe: Inderscience Research, 2024)
Multifunctional use of mini-football characterizes it as one of the most effective means of physical training of students. That is why the detailed analysis of the use of mini-football as a basic sport significantly contributes to the optimization of the educational process of physical education of university students.